ENVIRONMENTAL DETERMINANTS OF AGING. (11th November 2018) - Finch, C E; Martin, G
Abstract: Because the heritability the human lifespan is less than 35%, we must consider environmental factors in the individual outcomes of aging. This symposium considers urban air pollution and cigarette smoke as ubiquitous environmental toxins for interactions with aging. Both airborne toxins shorten lifespan and promote diseases of aging with dose-dependence. Dr. Jennifer Ailshire (USC) analyzed the Health Retirement Survey for biomarkers of aging that are sensitive to residential air pollution levels. Dr. Michele Block (Indiana U) identified pathways of inflammation, lung-to-brain that mediate the cognitive impact of air pollution. Dr. Carol Franz (UCSD) evaluated the Veterans Twin Study of Aging for brain region atrophy by smoking history. Lastly, Dr. Morgan Levine (Yale) identified the genetic and methylation signatures of older smokers. Together, these findings point to systemic and genomic responses to air pollution and smoking that are broadly shared by aging processes, lung to brain.